2017
DOI: 10.21608/adjalexu.2017.57868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Hyaluronic Acid Mixed With Biphasic Calcium Phosphate on Bone Healing Around Dental Implants (Experimental Study)

Abstract: INTRODUCTION:Biphasic calcium phosphate (BCP) is very widely used as a grafting material around dental implants. The properties of such material can be enhanced by adding interpositional graft materials to enhance osteoinduction. Hyaluronic acid (HyA) is an example of osteopromoting materials that can be added to the BCP to enhance its osteoinductive properties. OBJECTIVES: Histological evaluation of using HyA with BCP on bone healing around dental implants. MATERIALS AND METHODS:This study was a split mouth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…Our outcomes were in accordance with many studies [2], [16], [18] which concluded that HA enhances and fastens the repair time. Our findings were not corresponding to Mostafa et al [19] and Aebli et al [20] who stated that HA does not have any significant effect on healing time or repair capacity.…”
Section: Discussioncontrasting
confidence: 99%
“…Our outcomes were in accordance with many studies [2], [16], [18] which concluded that HA enhances and fastens the repair time. Our findings were not corresponding to Mostafa et al [19] and Aebli et al [20] who stated that HA does not have any significant effect on healing time or repair capacity.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, Hyaluronic acid was used in mixture with Osteon II collagen in group I to benefit from regenerative proprieties of HyA .This was in the same side of Shammal et al (18) and Aguado et al (19) who stated that HyA has osteoconductive activity; it accelerates the bone regeneration by means of chemo taxis, proliferation and successive differentiation of mesenchyme cells.…”
Section: Discussionmentioning
confidence: 61%
“…In the same context, several researchers (18,19) reported that Hyaluronic acid (HyA) capable to accelerate the onset of new bone formation when it is added to alloplastic bone graft for bone augmentation of alveolar defects. Where, HyA increases osteoblastic bone formation through increased mesenchymal cell differentiation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…These authors had used a mix of growth factors or bone morphogenic proteins with cancellous bone to improve osteogenic capacity of graft In the same context several researchers reported that HyA was capable to accelerate the onset of new bone formation when it is added to alloplastic bone graft for bone augmentation of alveolar defects. Where, HyA increases osteoblastic bone formation through increased mesenchymal cell differentiation and migration and decrease bone graft contamination (24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%